Republic of Croatia : Report on the Observance of Standards and Codes-Banking Supervision, Payment Systems, and Securities Regulation-Update. (IMF Staff Country Reports; Country Report, 2004)
This paper presents an update to the report on the Observance of Standards and Codes on Banking Supervision, Payment Systems, and Securities Regulation for Croatia. The 2001 Financial Sector Assessment Program (FSAP) mission assessed Croatia's compliance with the Basel Core Principles for Effective Banking Supervision (BCP). The results suggested that most of the core principles were either observed or broadly observed, the main exception being cooperation with foreign supervisory agencies, which was not possible under the then-existing legal framework.